Human rights and reproductive health: political realities and pragmatic choices for married adolescent women living in urban slums, Bangladesh - Rashid Sabina (BMC, 2011)
Abstract Background In Bangladesh, particularly in urban slums, married adolescent women's human rights to life, health, and reproductive and sexual health remain adversely affected because of the structural inequalities and political economic, social and cultural conditions which shape how rights are understood, negotiated and lived. Methods The focus of the research and methods was anthropological. An initial survey of 153 married adolescent women was carried out and from this group, 50 in-depth interviews were conducted with selected participants and, from the in-depth interviews, a further eight case studies of women and their families were selected for in-depth repeated interviews and case histories. Results This paper speaks of the unanticipated complexities when writing on reproductive rights for poor adolescent women living in the slums, where the discourses on 'universal human rights' are often removed from the reality of adolescent women's everyday lives. Married adolescent women and their families remain extremely vulnerable in the unpredictable, crime-prone and insecure urban slum landscape because of their age, gender and poverty. Adolescent women's understanding of their rights such as the decision to marry early, have children, terminate pregnancies and engage in risky sexual behaviour, are different from the widely accepted discourse on rights globally, which assumes a particular kind of individual thinking and discourse on rights and a certain autonomy women have over their bodies and their lives. This does not necessarily exist in urban slum populations. Conclusions The lived experiences and decisions made pertaining to sexual and reproductive health and 'rights' exercised by married adolescent women, their families and slum communities, allow us to reflect on the disconnect between the international legal human rights frameworks as applied to sexual and reproductive health rights, and how these are played out on the ground. These notions are far more complex in environments where married adolescent women and their families live in conditions of poverty and socioeconomic deprivation.